ANALISIS EFISIENSI USAHA TERNAK SAPI PERAH MENGGUNAKAN STOCHASTIC FRONTIER ANALYSIS - Luxy Lutfiana Rachmawati; Fitri Kartiasih (Center for Economic Studies Universitas Katolik Parahyangan, 2018)
The Milk Self-sufficiency Program that is targeted to be reached by the year of 2020 is threatened by the increasing of milk imports. Local milk production can only meet 18 to 20 percent of the national milk demand. This study aims to investigate the level of technical efficiency of the people's small hold farmers’ cattles in Java and to analyze factors that influence milk production using Stochastic Frontier Analysis. The results showed that the feed per animal per day had a positive effect on the average milk production per animal per day; while the size of cage per animal had a negative effect. The average level of efficiency of dairy cattle business in Java is 83.56 percent, but statistically there are effects of inefficiency in this business. Factors that influence the inefficiency of livestock businesses are: the farmer’s age, the farmer’s educational level, participation of the farmers in cooperatives and farmer groups.Keywords: dairy cows; Stochastic Production Frontier; technical efficiency